Novel nanofiber‐based material for endovascular scaffolds. Issue 3 (15th July 2014) - Wang, Rui; Levi‐Polyanchenko, Nicole; Morykwas, Michael; Argenta, Louis; Wagner, William D.
Abstract Conventional collagen‐based heart valves eventually fail because of insufficient replacement of graft material by host tissue. In this study, type I collagen was blended with silk fibroin and the synthetic elastic polymer poly (glycerol–sebacate) (PGS) in varying proportions to create multifunctional electrospun nanofibrous materials tailored for use as endovascular scaffolds such as heart valve replacement. Depending on the blended material the elastic moduli ranged from 2.3 to 5.0 Mpa; tensile stresses ranged from 0.8 to 1.5 Mpa; and strains ranged from 30% to 70%. Electrospun materials with a weight ratio of 4.5:4.5:1 (collagen, fibroin, and PGS) (termed PFC mats) were the most similar to native heart valves. In vitro degradation of PFC mats was 0.01% per week. Endothelial cells adhered to, proliferated, and formed cell–cell junctions on PFC mats. Compared with collagen hydrogels and electrospun collagen mats respectively 220–290% less platelet adhesion was observed for PFC mats. The study demonstrates that PFC material has superior mechanical properties, low degradation, and reduced thrombogenic potential and suggests that further investigation of this biomaterial for cardiovascular applications is warranted. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 1150–1158, 2015.